A proteomic investigation of isolated soy proteins with variable effects in experimental and clinical studies. - Gianazza, E; Eberini, I; Arnoldi, A; Wait, R; Sirtori, C (2003)
Dietary preparations of soy proteins used for clinical studies, particularly of hypercholesterolemia, in Europe and the United States were the subject of a proteomic comparison because differences in their composition may explain variability in experimental and clinical results. After two-dimensional electrophoresis, identities of the protein components (globulin subunits and their breakdown products) were established by matrix-assisted laser desorption/ionization mass spectrometry. The soy concentrates (Cholsoy/Croksoy), which were used in most of the Italian and Swiss studies in which reductions in cholesterolemia occurred, exhibited a predominance of breakdown products of the 7S globulin and mainly intact 11S globulin subunits. Soy isolates used in the United States (SUPRO) showed none of the major components corresponding to 7S globulin subunits; only some of the light chains of 11S were intact, and heavy chains of 11S also were fragmented. Ethanol- and nonethanol-treated SUPRO products showed considerable variability in their isoflavone concentrations and there seemed to be differential protein recoveries due to ethanol processing. These findings indicate differences in the protein composition of soy products used in clinical studies. We suggest that standardization should be improved before products are assessed for clinical outcome studies.